591The "Big 6": A purpose-based framework for motivating and teaching epidemiologic methods. (2nd September 2021) - Avelino-silva, Vivian; Zablotska, Lydia; Martin, Jeffrey
Abstract: Focus of Presentation: Many beginning students in health-related fields do not understand the types of questions that epidemiology can address. This results in underappreciation of the relevance of epidemiology. Even students dedicated to learning epidemiology and/or medicine have difficulty identifying the common features of disparate research questions and hence are limited in their ability to critique research. The reasons for these limitations are multifold, but we believe that traditional approaches of teaching epidemiology □ by study design □ is a substantial contributor. To better promote and deepen understanding of epidemiology, we have developed a purpose-based teaching approach called the "Big 6". Findings: In courses aimed towards graduate students in epidemiology and medical students, we now introduce what epidemiologic research can do and how to perform it according to the general purpose/goal/objective of research. We focus on six of the most common purposes/goals/objectives - the "Big 6". Conclusions: Introducing epidemiology according to general purposes of research (the "Big 6") gives students a framework to understand the relevance of epidemiology and rapidly critique the validity of epidemiologic research. Key messages: A purpose-based approach to teaching epidemiology may be more engaging and promote better understanding and application of epidemiologic methods.